2020
DOI: 10.1016/j.irfa.2019.101417
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric implied market volatility and terrorist attacks

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Schwert's (1989a) longitudinal U.S. study investigating volatility determinants noted particular periods of fluctuation in bond returns during the U.S. civil war (1861-65) and the Great War , with the situation being less pronounced for stock returns. When we search for a contemporary example for the supposed link, we find a study of Bevilacqua et al (2020), who observe an effect of terrorist incidents on the VIX index when decomposed into put and call options, with an impact in the former rather than the latter. Other studies empirically trace realized volatility responses to terror events (see, for instance, Arin et al (2008); Nikkinen and Vähämaa (2010); and Essadam and Karagianis (2014)).…”
Section: Impact Upon Volatilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Schwert's (1989a) longitudinal U.S. study investigating volatility determinants noted particular periods of fluctuation in bond returns during the U.S. civil war (1861-65) and the Great War , with the situation being less pronounced for stock returns. When we search for a contemporary example for the supposed link, we find a study of Bevilacqua et al (2020), who observe an effect of terrorist incidents on the VIX index when decomposed into put and call options, with an impact in the former rather than the latter. Other studies empirically trace realized volatility responses to terror events (see, for instance, Arin et al (2008); Nikkinen and Vähämaa (2010); and Essadam and Karagianis (2014)).…”
Section: Impact Upon Volatilitymentioning
confidence: 99%
“…We then extend the modeling beyond the historical perspective and examine the forwardlooking VIX index. The link between implied volatility and national security concerns has only been examined once in the prior literature (see Bevilacqua et al, 2020). The extant evidence shows that, in the face of terrorism, stock returns exhibit significantly elevated realized volatility, which is relatively short-lived (Essaddam and Mnasri, 2015).…”
Section: Impact Upon Volatilitymentioning
confidence: 99%
“…Recent studies have found empirical evidence on the impact of terrorism on stock returns. These include Gok et al (2020) in Turkey, Khan and Ahmed (2019) in Pakistan, Bevilacqua et al (2019) in developed countries, Chaudhry et al (2018) in SAARC region and in Europe. These studies reported adverse impacts of terrorist attacks on financial market and economic development for their respective sample countries.…”
Section: Socio-political Turbulence and Firm Riskmentioning
confidence: 99%
“…They further showed that events that occurred within the U.S. appear to impact both VIX and VIX− in a similar way, whereas international terrorist attacks showed a greater impact on the puts component, VIX−. The calls component, VIX+, was found to be mainly detached from terrorist attacks [ 8 ]. Balcells assessed the effect of terrorism on public support for political parties and individuals’ willingness to participate in democratic elections and found that attacks were likely to increase individuals’ intent to participate in democratic elections but not to change their vote choice as reported in the surveys [ 9 ].…”
Section: Introductionmentioning
confidence: 99%